The Quest for Meaning in Life in 20th-Century British Novels: A Stylistic Analysis of Virginia Woolf's The Waves - Djebali, Hana; Rouiha, Farid (University of Eloued جامعة الوادي, 2024)
Abstract This dissertation examines the theme of the quest for meaning in Virginia Woolf's The Waves through a stylistic analysis. The aim of this research is to explore the stylistic features Woolf employed to convey her theme. The study adopts a descriptive analytical method, applying Geoffrey Leech and Mick Short's literary stylistic approach. The primary data for the analysis comes from Woolf's The Waves, which serves as the foundation for examining Woolf's narrative techniques and their impact on the thematic depth of the novel. The dissertation consists of three chapters: the first provides a theoretical overview of the historical background of modernism in 20th-century British literature; the second presents Leech and Short's approach as outlined in Style in Fiction; and the third chapter offers a practical analysis, including a summary of the novel, its themes, literary devices, and character analysis. The study concludes that The Waves offers a profound exploration of the quest for meaning in life through the complex lives of its six main characters. تحاول هذه الأطروحة دراسة موضوع البحث عن المعنى في الحياة بدراسة رواية الأمواجلفرجينيا وولف باستخدام تحليل أسلوبي. الغرض من هذا البحث هو مناقشة الميزة الأسلوبية التي استخدمتها وولف للتعبير عن موضوعها. تم اتباع طريقة تحليلية وصفية باستخدام منهج جيفري ليتش و ميك شورت في الأسلوب الأدبي القصير،و تم أخذ البيانات الأولية للدراسة من رواية "الأمواج "كأساس لتحليل الأسلوبي في الرواية. وقد ركزت الدراسة على تقديم رؤى قيمة حول تقنيات وولف السردية وتأثيرها على العمق الموضوعي للرواية.كما أن هذه الدراسة تتكون من ثلاثة فصول، الفصل الأول يتناول النظرية الخلفية التاريخية للحداثة في الأدب البريطاني في القرن 20، أما عن الفصل الثاني فقد تضمن مقاربة ليتش وشورت في كتاب الأسلوب في الرواية ، بينما يشمل الجزء العملي ملخصا لهذه الأخيرة، ومواضيعها، والأدوات الأدبية المستخدمات، وتحليل الشخصيات. أظهرت نتائج الدراسة أن الأمواج تقدم استكشافا عميقا لموضوع البحث عن معنى الحياة من خلال عرض صور مختلفة للحياة عبرالشخصيات الرئيسية.
Literature and Civilization
Keywords: Virginia Woolf; The Waves; Leech and Short approach; stream of consciousness; modernism; stylistic analysis; فرجينيا وولف ، الأمواج ، مقاربات ليتش وشورت ، تيار الوعي ، الحداثة ، التحليل الأسلوبي ، البحث عن معنى في الحياة